2008
DOI: 10.3324/haematol.11867
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor promotes migration of human myeloma cells

Abstract: Multiple myeloma is characterized by the accumulation and dissemination of malignant plasma cells in the bone marrow. Cell migration is thought to be important for these events. We studied migration in a Transwell two-chamber assay and tested the motogenic effect of various cytokines. In addition to insulin-like growth factor-1 and stromal cell-derived growth factor-1α, previously known as chemoattractants for myeloma cells, we identified hepatocyte growth factor as a potent attractant for myeloma cells. Hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 21 publications
4
30
0
Order By: Relevance
“…15,[29][30][31][32] Its cytoreductive activity was also demonstrated in a gastric carcinoma xenograft model. 29) These in vitro and in vivo studies support the therapeutic potential of targeting MET in cancers where MET plays a role in tumor growth or metastasis.…”
Section: Met-targeted Therapymentioning
confidence: 99%
“…15,[29][30][31][32] Its cytoreductive activity was also demonstrated in a gastric carcinoma xenograft model. 29) These in vitro and in vivo studies support the therapeutic potential of targeting MET in cancers where MET plays a role in tumor growth or metastasis.…”
Section: Met-targeted Therapymentioning
confidence: 99%
“…Moreover, it may account for the increased microvessel density observed in the BM [5][6][7] . Hepatocyte growth factor (HGF) produced by myeloma cells is a pleiotropic cytokine which promotes tumor cell growth, bone marrow dissemination, inhibits osteoblast function and contributes to myeloma bone disease and BM angio- 8 . Migration and invasion of myeloma cells require the secretion of metaloproteinase-2 (MMP-2) and MMP-9 which are possibly modulated, in part, by syndecan-1 (CD 138 ), expressed in plasma cells and which can be shed from the surface of myeloma cells and circulate as soluble factor 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, cytoskeletal activation downstream from mTORC2 has been suggested via Rho and other related proteins (16), which are consistent with our observation at a later time point of RAPA induced GBM motility. Alternatively, a study using a transwell two-chamber migration assay indicated that cytokine-induced cell migration did not involve mTOR in cancer cells (43).…”
Section: Discussionmentioning
confidence: 99%